Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica - Goel, Vikram; Brown, Joel; Matsuoka, Kenichi (The Cryosphere, 2017)
The ice-shelf-fringed coast of Dronning Maud Land in East Antarctica contains numerous ice rises that influence the dynamics and mass balance of the region. However, only a few of these ice rises have been investigated in detail. Here, we present field measurements of Blåskimen Island, an isle-type ice rise adjacent to Fimbul Ice Shelf. This ice rise is largely dome shaped, with a pronounced ridge extending to the south-west from its summit (410 m a.s.l.). Its bed is mostly flat and about 100 m below the current sea level. Shallow radar-detected isochrones dated with a firn core reveal that the surface mass balance is higher on the south-eastern (upwind) slope than on the north-western (downwind) slope by ∼ 37 %, and this pattern has persisted for at least the past decade. Moreover, arches in radar stratigraphy suggest that the summit of the ice rise has been stable for ∼ 600 years. Ensemble estimates of the mass balance using the input–output method show that this ice rise has thickened by 0.12–0.37 m ice equivalent per year over the past decade.